Influence of alfalfa harvesting and storing methods on steer performance - K.K. Bolsen; L.L. Berger; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1974)
Three alfalfa treatments were evaluated in a steer performance trial: (1) direct-cut and ensiled with dry milo, (2) field-wilted and ensiled, with milo added at feeding and (3) baled, with milo added at feeding. The rations contained 45.4, 50.9 and 48.1 percent milo, respectively. During the 84-day trial, yearling steers made similar gains on the three rations. Direct-cut and ensiled alfalfa produced the most efficient gain; hay the least efficient. Potential beef gain per acre of alfalfa was lowest from baled hay.
Keywords: Cattlemen& #x27; s Day; 1974; Report of progress (Kansas State University. Agricultural Experiment Station); 210; Beef; Alfalfa; Steer; Performance